Rapid heating rates define the volatile emission and regolith composition of (3200) Phaethon - Suttle, MD; Olbrich, LF; Bays, CL; Riches, L (Nature Research, 2024)
Asteroid (3200) Phaethon experiences extreme solar radiant heating ( ~ 750 °C) during perihelion (0.14 au), leading to comet-like activity. The regolith composition and mechanism of volatile emission are unknown but key to understanding JAXA’s DESTINY+ mission data (fly-by in 2029) and the fate of near-Sun asteroids more generally. By subjecting CM chondrite fragments to fast, open system, cyclic heating (2-20 °C/min), simulating conditions on Phaethon we demonstrate that rapid heating rates combine with the low permeability, resulting in reactions between volatile gases and decomposing minerals. The retention of S-bearing gas limits the thermal decomposition of Fe-sulphides, allowing these minerals to survive repeated heating cycles. Slow escape of S-bearing gases provides a mechanism for repeated gas release from a thermally processed surface and, therefore the comet-like activity without requiring surface renewal to expose fresh material each perihelion cycle. We predict Phaethon regolith is composed of olivine, Fe-sulphides, Ca-sulphates and hematite.